(untitled) (Bangladesh Journal of Botany, 2014)
Bacillus cereus LW-17 enhanced net regeneration of dissolved inorganic nitrogen and phosphorus in the Gulshan lake water by about two-folds at temperatures of 26°C and 30ºC, respectively. Application of Bacillus cereus LW-17 would be promising for improvement of polluted environment. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18043 Bangladesh J. Bot. 42(2): 349-353, 2013 (December)